2013
DOI: 10.1016/j.jpedsurg.2012.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal factors associated with poor neurocognitive outcome in early school age congenital diaphragmatic hernia survivors

Abstract: Objective Determine predictors of neurocognitive outcome in early school age congenital diaphragmatic hernia (CDH) survivors. Study design Prospective study of infants with CDH at Duke University Medical Center. Neurocognitive delay (NCD) at school age (4 to 7 years) was defined as a score < 80 in any of the following areas: Verbal Scale IQ, Performance Scale IQ, Expressive Language, or Receptive Language. Logistic regression, Fisher’s exact, and the Wilcoxon rank sum test were used to examine the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…This is consistent with Friedman et al who reported VT as the only independent predictor of motor problems at 12 months in CDH survivors [4]. Benjamin et al found that duration of mechanical ventilation was predictive of neurocognitive delay at early school age while Danzer in a longitudinal study reported that in the first 3 years of life prolonged ventilation tended to be associated with persistent adverse neuromotor outcome [15,17].…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with Friedman et al who reported VT as the only independent predictor of motor problems at 12 months in CDH survivors [4]. Benjamin et al found that duration of mechanical ventilation was predictive of neurocognitive delay at early school age while Danzer in a longitudinal study reported that in the first 3 years of life prolonged ventilation tended to be associated with persistent adverse neuromotor outcome [15,17].…”
Section: Discussionsupporting
confidence: 84%
“…After screening of title/abstract followed by full text, 23 papers 6,7,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] reporting on 895 children met our inclusion and exclusion criteria and were selected for systematic review (Table 1). There was a wide range in follow-up duration and time of assessment from 12 months up to 60 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…Risk factors that negatively influence neurodevelopment include low birth weight, 6 higher number of congenital anomalies, 7 a longer hospital stay, 7,26,28,40 duration of mechanical ventilation, 29,31,35,40,42 and need for supplemental oxygen at discharge. 26 However, data to evaluate longer-term neurocognitive outcomes associated with these risk factors were limited in the studies that were included in this review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations